Modulated speckle simulations based on the random-walk model - Lencina, Alberto (2003)
The random walk model is employed to simulate modulated speckle patterns. We demonstrate that the geo metrical image approximation fails to describe the modulated speckle pattern. A new approach to analyzing this phenomenon is proposed. The validity of the approximations employed is verified by comparison of the simulation with the experimental results. Speckle metrological applications and phase measurement tech niques could be improved by taking advantage of this model.